The Staphylococcus Aureus Toxins and its Pathogenesis: A Review - Hashem Shehab, Zina; Al-Shimmary, Sana; Thanoon Ahmed, Shatha (Al-Nahrain Journal of Science, 2024)
Staphylococcus aureus is a grave community-acquired and nosocomial pathogen related to elevated levels of morbidity and mortality and produces a high number of toxins and other virulence agents. So, our review focuses on how S. aureus begins, colonizes, and causes the infection and upon the main determinants involved. This bacterium toxins included different types like (Alpha, Beta, Gamma, and Delta) Hemolysins, Leukotoxins, Staphylococcal Enterotoxins (SEs), Exfoliate Toxins (ETs) , Toxic-Shock Syndrome Toxin (TSST) and Toxin-antitoxin (TA) systems.. Studying the determinants of staphylococcal virulence and determining its structure,  function, and epidemiology will facilitate the development of strategies to eliminate its resistance to antibiotics, especially in the absence of an anti- S. aureus vaccine.